Etoricoxib – the possibility of its use in the practice of the general practitioner - Mastalerz-Migas, Agnieszka; Kwiatkowska, Brygida; Majdan, Maria; Niewada, Maciej; Skrzydło-Radomańska, Barbara; Mamcarz, Artur (Lekarz POZ, 2017)
Pain is an inherent element of rheumatoid diseases and significantly worsens the quality of life of the patients. Therefore, patients with pain conditions in osteoarthritis (OA), rheumatoid arthritis (RA), ankylosing spondylitis or gout should receive efficient pain management. Selection of an effective and safe drug for the patient is a great challenge for the general practitioner. Difficulties in selecting the best drug apply mainly to patients with comorbidities, especially the elderly because in that group of patients the risk of drug interactions and potential complications is significantly greater. For patients with a high risk of gastroenterological complications or in the case of concerns about hepatotoxicity of nonsteroidal anti-inflammatory drug (NSAID) therapy, with a low cardiovascular risk, coxibs, including Etoricoxib should be the first-choice drugs.